SURVEI KETERAMPILAN SOSIAL SISWA PADA PEMBELAJARAN PPKN DI KELAS TINGGI SDN 07 PETUKANGAN UTARA - Rahmadina, Siti; Zakiah, Linda; Sumantri, M. Syarif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
During learning, there needs to be special attention to student social skills. The reason is that having social skills can have an influence on student activeness in learning. In this context, Civics learning is one of the lessons related to student social skills, because there are more aspects related to social, such as multicultural community relations. Based on that, the purpose of this research is to find out how much the level of student social skills in Civics learning. This research is a quantitative research with survey method. The subjects of this study were high class students who totaled 100 students. Sampling using simple random sampling technique. Data collection was carried out by filling out a questionnaire. The results showed a correlation between social skills and Civics learning. Proven by the results of the study which are categorized as